„Úgy veszem, hogy itt jártak…” Egy elmaradt püspöki látogatás margójára - Alfréd SOMOGYI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2021)
“I Take It as If They Were Here…” A Side-Note on a Cancelled Episcopal Visitation. The study examines a letter which has extraordinary importance for the Re-formed community in Czechoslovakia. It was written on behalf of President Tomáš Garrique Masaryk to the bishops of the Reformed Church in 1922. At that point in history, the Hungarian Reformed people, who came under the new rule of an entirely new state, Czechoslovakia, were able to form their new ecclesiastical dioceses. However, an independent Reformed Church of Czecho-slovakia had not yet been proclaimed since they were not able to convene a syn-od. The leaders of the church tried to make use of all kinds of political connec-tions to serve the need of the church. Therefore, they initiate a meeting with President Masaryk, who was having a holiday in Kistapolcsány (Topolčianky) during the autumn of 1922. All preparations made seemed to be organized well and go smoothly, even the lobby executed in the political arena indicated that the much-expected meeting would take place. However, the au-dience was cancelled by the office of the head of the state during the very last meeting. This study investigates the preparations of the meeting, tries to assess on the basis of historical sources its assumed significance, and offers a reflection about the possible reasons why the hearing had been cancelled.